2017
DOI: 10.1007/s00421-017-3781-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exertional-heat stress on gastrointestinal integrity, gastrointestinal symptoms, systemic endotoxin and cytokine profile

Abstract: Exertional-heat stress induces a thermoregulatory strain that subsequently injures the intestinal epithelium, reduces endotoxin clearance capacity, promotes greater cytokinaemia, and development of gastrointestinal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 68 publications
12
118
1
5
Order By: Relevance
“…A previous systematic review has suggested an exercise‐induced hyperthermia threshold of 38.6°C T core for GI barrier integrity loss (DSAT, I‐FABP and endotoxin) to be commonplace (>50% incidence) and of 39.0°C for GI barrier integrity loss to be universal (100% incidence; Pires et al, ). Consistently, previous research supports the notion that MT biomarkers (endotoxin) are less responsive to subtle alterations in GI barrier integrity that were otherwise detected by the DSAT or I‐FABP following exercise (March et al, ; Snipe et al, , ). Positively, no GI barrier integrity or MT biomarker displayed statistical heteroskedasticity in this EHST model, suggestive that absolute reliability was not dependent upon the magnitude of biomarker response.…”
Section: Limitationssupporting
confidence: 78%
See 1 more Smart Citation
“…A previous systematic review has suggested an exercise‐induced hyperthermia threshold of 38.6°C T core for GI barrier integrity loss (DSAT, I‐FABP and endotoxin) to be commonplace (>50% incidence) and of 39.0°C for GI barrier integrity loss to be universal (100% incidence; Pires et al, ). Consistently, previous research supports the notion that MT biomarkers (endotoxin) are less responsive to subtle alterations in GI barrier integrity that were otherwise detected by the DSAT or I‐FABP following exercise (March et al, ; Snipe et al, , ). Positively, no GI barrier integrity or MT biomarker displayed statistical heteroskedasticity in this EHST model, suggestive that absolute reliability was not dependent upon the magnitude of biomarker response.…”
Section: Limitationssupporting
confidence: 78%
“…In general, no GI barrier integrity and MT biomarkers, except DSAT 150 and Δ LBP, were found to correlate. Previous exercise gastroenterology research has shown various combinations of these biomarkers to correlate weakly (r = 0.1-0.6; Yeh et al, 2013;Sessions et al, 2016;March et al, 2019) or not at all (Karhu et al, 2017;Snipe, Khoo, Kitic, Gibson, & Costa, 2018). Several physiological (e.g.…”
Section: F I G U R E 4 Gi Mt Responses To Ehstmentioning
confidence: 99%
“…Literature that is able to differentiate between the impact of environmental temperature and exercise intensity on associated intestinal damage is scarce. Previously, it has been shown that when exercising at the same absolute intensity, increasing environmental temperature is associated with greater increases in intestinal damage (Snipe et al 2016;Snipe et al 2018a). Snipe et al (2016) reported a greater increase in I-FABP level when running at the same absolute speed in 30°C compared to 22°C; however, it was unknown whether this increase in damage was attributable to the greater exercise strain that accompanies exercise in the heat at the same absolute intensity, or to the increase in environmental temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been difficult to determine the influence of environmental heat on intestinal damage as studies often combine increasing temperature with increasing physiological demand (Maw et al 1993), making it difficult to isolate the effects of the environment. Snipe et al (Snipe et al 2016;Snipe et al 2018a) have reported a dose response in post-exercise intestinal damage, as measured by I-FABP, with increasing environmental temperature from 22°C to 30°C and 22°C to 35°C. While the damage may in part be attributed to increasing ambient temperature, participants were running at the same absolute treadmill speed during each trial and as such exercise intensity may have differed in the hot versus temperate conditions given the possible increased physiological strain and metabolic cost of exercising in the heat (No and Kwak 2016;Collins et al 2017).…”
Section: Page 3 Of 26mentioning
confidence: 99%
See 1 more Smart Citation